Decerebration induced by surgical transection of cerebral ganglion of crayfish - Mera, Baltazar Barrera; Ortega, Emilio Pérez; Ruiz, Rodrigo Banegas; Caprielova, Yuri Jiménez; Gómez Mendoza, Francisco Fabián; Mendoza Aceves, Rodrigo A.; Valderrama Treviño, Alan I. (International Journal of Research in Medical Sciences, 2020)
Background: Since the neural structures of the crayfish brain closely resemble their equivalent in the mammals. This can be suggested by observing the similarity that exists in the brain divided by the surgical transection of the crayfish brain in which the protocerebrum remains attached to the first two cranial nerves, findings also described by Frederic Bremer in 1935 in cats with cerebral transection. Methods: Total 11 Adult male crayfish were trained to respond with defense reflex, the animals were placed in water at 0°C, remained without any movement, and subsequently through a small incision of 3 mm in diameter in the medial antero region and dorsal cephalothorax region, a surgical section of the cerebral ganglion was performed. Immediately after surgery, metal microelectrodes were implanted to collect the activity of the photoreceptors and visual fibers. Results: Once the defense reflex begins to recover in previously decerebrated crayfish, it means that it shows signs of reconnection. The isolated protocerebrum with the deutocerebrum olfactory lobe remain alive for several days and the neuronal connections were reestablished, as measured throughout the bilateral defense activity. The defense reflex was observed in all animals and then recovered after surgery. Conclusions: The crayfish is an excellent model to work the visual activity, all coding of visual information was suppressed in de-cerebrated crayfish. The recovery of the neural disconnection is observed from 40 days, where the defence reflex appears again before visual stimuli.